Allele Mining and Selective Patterns of Pi9 Gene in a Set of Rice Landraces from India - Imam, Jahangir; Mandal, Nimai P.; Variar, Mukund; Shukla, Pratyoosh (Frontiers in Plant Science, 2016)
Allelic variants of the broad-spectrum blast resistance gene, Pi9 (nucleotide binding site-leucine-rich repeat region) have been analyzed in Indian rice landraces. They were selected from the list of 338 rice landraces phenotyped in the rice blast nursery at central Rainfed Upland Rice Research Station, Hazaribag. Six of them were further selected on the basis of their resistance and susceptible pattern for virulence analysis and selective pattern study of Pi9 gene. The sequence analysis and phylogenetic study illustrated that such sequences are vastly homologous and clustered into two groups. All the blast resistance Pi9 alleles were grouped into one cluster, whereas Pi9 alleles of susceptible landraces formed another cluster even though these landraces have a low level of DNA polymorphisms. A total number of 136 polymorphic sites comprising of transitions, transversions, and insertion and deletions (InDels) were identified in the 2.9 kb sequence of Pi9 alleles. Lower variation in the form of mutations (77) (Transition + Transversion), and InDels (59) were observed in the Pi9 alleles isolated from rice landraces studied. The results showed that the Pi9 alleles of the selected rice landraces were less variable, suggesting that the rice landraces would have been exposed to less number of pathotypes across the country. The positive Tajima’s D (0.33580), P > 0.10 (not significant) was observed among the seven rice landraces, which suggests the balancing selection of Pi9 alleles. The value of synonymous substitution (-0.43337) was less than the non-synonymous substitution (0.78808). The greater non-synonymous substitution than the synonymous means that the coding region, mainly the leucine-rich repeat domain was under diversified selection. In this study, the Pi9 gene has been subjected to balancing selection with low nucleotide diversity which is different from the earlier reports, this may be because of the closeness of the rice landraces, cultivated in the same region, and under low pathotype pressure.